Study of meteorological parameters for cloud analysis - Lee, Chen (2017)
In this project, various approaches were taken to analyse the different cloud detection models available in order to find methods to improve on them. Weather data obtained from both radiosondes and meteorological stations (METAR data) were used in this analysis. Having no prior knowledge of meteorological data, the first task would be to conduct some basic research on such data. Following which, studies were conducted on how meteorological data can be obtained and analyzed. This was done by studying equipment and charts like radiosondes and Skew T plots respectively. After gaining a better understanding on the research topic, the next course of action was to find out the different models of cloud detection. This serves as a preparation for the next step which is to analyse data obtained from radiosondes. From the analyzed data, the relation between various parameters like water vapor pressure and relative humidity were studied against altitude. MatLab is used as the program of choice to examine this relationship. This research will serve as a solid background for the identification of clouds from radiosonde and METAR data. Following which, the Water Vapor Pressure (WVP) cloud detection model will be examined to see how it can be applied globally to cover Sub-Tropical and Temperate regions as well. The original study for the WVP model had only covered on readings for Tropical regions. Results obtained from this study will conclude how differing regions can have dissimilar amounts of cloud presence. Last but not least using METAR data, the cloud altitudes of different regions will also be researched upon. Each region will be further narrowed down into mainland, island and coastal areas to determine if an area’s distance from the sea will affect its cloud altitudes. Analysis on Cloud Base Height (CBH) will also be done to back this study.